2001
DOI: 10.1080/03079450120066421
|View full text |Cite
|
Sign up to set email alerts
|

Protection of chickens against renal damage caused by a nephropathogenic infectious bronchitis virus

Abstract: The ability of the infectious bronchitis (IB) Ma5 and 4/91 live-attenuated vaccines to protect against kidney damage caused by a nephropathogenic strain of IB virus (B1648) was investigated. Protection parameters considered were gross and microscopic renal pathology, and the use of a polymerase chain reaction to detect IB RNA in kidney tissue. By each parameter, Ma5 vaccine alone provided poor protection, but 4/91 alone or the combined program both protected well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 17 publications
3
68
0
4
Order By: Relevance
“…Some IBV strains are intrinsically nephropathogenic i.e. they reproducibly cause nephritis when inoculated experimentally into specific pathogen free chickens, causing mortality [30,63,64,81]. IBV infects mainly the lower nephron down to the collecting duct epithelial cells [25,26].…”
Section: Pathogenesis Of Ibvmentioning
confidence: 99%
“…Some IBV strains are intrinsically nephropathogenic i.e. they reproducibly cause nephritis when inoculated experimentally into specific pathogen free chickens, causing mortality [30,63,64,81]. IBV infects mainly the lower nephron down to the collecting duct epithelial cells [25,26].…”
Section: Pathogenesis Of Ibvmentioning
confidence: 99%
“…Extensive clinical experience and laboratory studies have shown that vaccination with two or more different live attenuated IBV vaccines confers a broad protection against many important heterologous serotypes (Cook et al, 1999(Cook et al, , 2001Worthington et al, 2004). This has led to the ''protectotype'' concept, according to which significant cross-protection can be obtained by using strains that are dominant antigenically.…”
Section: Introductionmentioning
confidence: 99%
“…Although these recent papers give us a valuable insight into the genetic epidemiology of IBV in Brazil, they lack data concerning serotyping, pathotyping and protection provided by vaccination against the recent Brazilian IBV strains. It has been shown in several papers reporting the level of homology of the S1 gene (or a part of it) and the level of cross-protection that there is on average a higher chance of a good level of cross-protection between strains with a high level of homology than between strains with low homology (Cavanagh et al, 1997;Cook et al, 2001;Meir et al, 2004;Gelb et al, 2005;Ladman et al, 2006). However, all data together show that this relationship is rather weak (De Wit et al, 2011a).…”
Section: Introductionmentioning
confidence: 55%